Worker reallocation over the business cycle: a comprehensive study of the Portuguese labor market - Rau, Simon (2022)
This master thesis uses Portuguese employee-employer matched data covering more than 30 years to analyze worker flows over the business cycle, taking into account firm heterogeneity. The results show that Portugal has experienced declining worker flows over the past 30 years, which can generally be attributed to declining hiring rates through non-employment. Using AKM firm premia to create firm clusters by productivity, I find that firms contribute differently to the reallocation of workers in recessions depending on their rank in the firm productivity distribution. My results give no evidence of a cleansing effect that reallocates workers from low-productivity firms to high-productivity firms. Recessions have a negative impact on worker flows with firms adjusting employment through hiring fewer workers and increasing job-to-job worker reallocation. The decrease of hiring workers from non-employment can be explained by high employment regulation, which drives up firms' costs of adjusting employment, making adjustment through the firing channel more difficult. Overall, low-productivity firms adjust less likely to business cycles than high-productivity firms. My conjecture that small, unproductive firms are less exposed to national and international competition, employ workers who are less likely to change jobs because of their characteristics, and thus are less likely to adjust to business cycles needs to be the subject of future research.1